Pengaruh Tax Amnesty Terhadap Sengketa Pajak : (Studi pada salah satu Lembaga Pemerintahan) - Sandra Septelia; Maulana Yusup; Robbi Saepul Rahman; S Mia Lasmaya (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
Tax Amnesty expects to improve tax compliance due to more effective supervision, supported by more accurate information regarding the list of taxpayer assets. From the initial data obtained, an anomaly obtained that in 2012 – 2017 there is a lower tendency for tax disputes when compared to the year after implementing the tax amnesty, namely 2018 and 2019. This study aims to determine and analyze the magnitude of the Effect of Tax Amnesty on Tax Disputes. The population in this study is a tax dispute with 21 respondents/defendants. Determining the sample in this study is based on the purposive sampling method. The data testing technique uses simple linear regression with a significant level of 5% alpha. Based on the study results, Tax Amnesty has a significant effect on Tax Disputes.